Associations of reproductive breast cancer risk factors with expression of stem cell markers in benign breast tissue - Yaghjyan, Lusine; Heng, Yujing J.; Baker, Gabrielle M.; Bret-Mounet, Vanessa C.; Murthy, Divya; Mahoney, Matt B.; Rosner, Bernard; Tamimi, Rulla M. (Frontiers in Oncology, 2024)
Background We investigated the associations of reproductive factors known to influence breast cancer risk with the expression of breast stem cell markers CD44, CD24, and ALDH1A1 in benign breast biopsy samples. Methods We included 439 cancer-free women with biopsy-confirmed benign breast disease within the Nurses’ Health Study (NHS) and NHSII. The data on reproductive and other breast cancer risk factors were obtained from biennial questionnaires. Immunohistochemistry (IHC) was performed on tissue microarrays. For each core, the IHC expression was assessed using a semi-automated platform and expressed as % of cells that stained positive for a specific marker out of the total cell count. Generalized linear regression was used to examine the associations of reproductive factors with a log-transformed expression of each marker (in epithelium and stroma), adjusted for other breast cancer risk factors. Results In multivariate analysis, the time between menarche and age at first birth was inversely associated with CD44 in epithelium (β per 5 years = −0.38, 95% CI −0.69; −0.06). Age at first birth and the time between menarche and age at first birth were inversely associated with ALDH1A1 (stroma: β per 5 years = −0.43, 95% CI −0.76; −0.10 and β = −0.47, 95% CI −0.79; −0.15, respectively; epithelium: β = −0.15, 95% CI −0.30; −0.01 and β = −0.17, 95% CI −0.30; −0.03, respectively). Time since last pregnancy was inversely associated with stromal ALDH1A1 (β per 5 years = −0.55, 95% CI −0.98; −0.11). No associations were found for CD24. The observed associations were similar in premenopausal women. In postmenopausal women, lifetime duration of breastfeeding was inversely associated with stromal ALDH1A1 expression (β for ≥24 vs. 0 to <1 months = −2.24, 95% CI 3.96; −0.51, p-trend = 0.01). Conclusion Early-life reproductive factors may influence CD44 and ALDH1A1 expression in benign breast tissue.